Economic Costs Associated to the Coronavirus Pandemic for Vietnam - Morisset, Jacques (World Bank, Washington, DC, 2020)
The short-term impact of coronavirus outbreak (i.e., 2019-nCov) on Vietnam’s economy could be significant, as high 6-10 percent of monthly output, but short-lived if the outbreak is rapidly contained. While the recent measures by the Government to limit the mobility of people, goods, and services with China will help to prevent the outbreak from spreading to Vietnam, they come with some economic costs. Tourism and electronics trade are the most vulnerable, with one-third of foreign tourists are from China and with over 3 billion dollars per month of bilateral trade between the two countries. The direct costs to contain the epidemic remains relatively small but could increase rapidly if the outbreak spreads within Vietnam, restrictions on mobility are sustained over time and if people behavior amplifies the initial negative impacts. Lessons from experience of recent pandemic show that while the negative costs could be high, the economy tends to recover rapidly once the outbreak is contained. The estimates presented here are highly dependent on assumptions regarding the magnitude and the duration of the epidemic and should be considered as preliminary.